THM model of rock tunnels in cold regions and numerical simulation - Liu, Naifei; Liang, Shihao; Wang, Shuangjie; Song, Zhanping (Scientific reports, 2024)
The freezing damage of rock tunnels in cold region involves ice-water phase change and complicated interaction of Thermo–Hydro–Mechanical (THM) field. Taking the fractured rock mass of cold region tunnels as research subject, the THM coupling model of cold region tunnels was established, which is based on the seepage mechanics, heat transfer theory, damage mechanics and equivalent continuum theory. This model could reflect the anisotropic properties of deformation, water migration and heat transfer caused by the initial fracture of rock mass. The construction and operation processes of a rock tunnel in cold region were simulated, and results were compared with the measured value and predecessor’s achievements. It shows that proposed model could reflect the anisotropic property of surrounding rock and the simulated deformation and stress are not symmetrical. Compared with the literature, the calculated results in this paper are closer to the measured values. The insulating layer has a significant effect on the stress of the supporting structures. The maximum tension stress of the lining is 4.5 times as that without insulating layer, and the lining will be destroyed for the overlarge tension stress.